Crystal structure and magnetism of colossal dielectric oxides DyxSr2−xTiMnO6 (x = 0‚ 0.5). (26th October 2018) - Mondal, Rajib; Biswas, Kalyan; Ghosh, Tapas; Fabitha, K; Rao, M S Ramachandra; Morozkin, A V; Nigam, A K; Quezado, S; Malik, S K; Nirmala, R
Abstract: Polycrystalline Dyx Sr2−x TiMnO6 (x = 0, 0.5) double perovskite oxides crystallize in cubic structure (Space group Fm- 3 m, No. 225) at room temperature. The oxide Sr2 TiMnO6 orders antiferromagnetically at ∼14 K (TN ) below which zero-field-cooled and field-cooled magnetization data show bifurcation. Magnetization of the sample Dy0.5 Sr1.5 TiMnO6 shows only a tendency to order around 3 K and no clear signature of magnetic ordering. The magnetization value at 2 K is greatly enhanced in the Dy-substituted sample compared to that in parent Sr2 TiMnO6 . The real part of the dielectric permittivity of both Dyx Sr2−x TiMnO6 (x = 0, 0.5) oxides are of the order of 10 4 at room temperature. The colossal dielectric constant values in these oxides could be understood in terms of intrinsic hopping conduction and extrinsic Maxwell-Wagner relaxation mechanism. Powder x-ray diffraction data confirm that Sr2 TiMnO6 does not undergo any structural transition in the temperature range of 300 K to 800 K and reveal normal thermal expansion behaviour. X-ray photoelectron spectroscopy data on Dy0.5 Sr1.5 TiMnO6 indeed confirm the presence of mixed valence states for Mn (Mn 3+ and Mn 4+ ) as expected from magnetization measurements. Thus rare earth ion substitution at Sr-site of Sr2 TiMnO6 is a sensitive method to tune the magnetic properties while preserving the colossal dielectric property.